"A Long Poem of Walking": Flâneurs, Vendors, and Chronicles of Post-abolition Rio de Janeiro. (January 2014) - Acerbi, Patricia
Chronicle literature in early twentieth-century Rio de Janeiro developed in tandem with the urban modernization that followed the abolition of slavery in 1888. Writers-flâneurs strolled city streets to observe human behavior in the new post-abolition urban environment. The street vendor, a fellow traveler within the city, was quickly identified by chroniclers as an integral component of the modern city. Ruling elites, however, viewed street commerce as a blot on the modern urban landscape and sought to prohibit vending through a series of policies that vendors often contested. Chroniclers and newspapers' embrace of vendors therefore reveals the ambivalence that marked the effort to define modernity. Although connected to the city's slave past, street vendors came to represent a modern urban membership unique to the Brazilian capital. The practice of street commerce and the intellectual culture surrounding it reflects how "walking the city" carved an alternative urban citizenship and sense of belonging.